2019
DOI: 10.1177/2309499019848079
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized study comparing navigation versus conventional total knee arthroplasty

Abstract: Background: Navigation is associated with improved accuracy in alignment. However, its influence on clinical outcome is inconclusive. The aim of this study was to compare the component alignment and functional outcome in patients undergoing navigation-assisted and conventional total knee replacement (TKR). Materials and method: A prospective randomized study consisting of two groups (group A and group B) was carried out. Group A consisted of patients undergoing TKR using conventional jig-based method, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…While Harvie et al reported no difference in functional outcome (Knee society, SF 36, WOMAC scale and patient satisfaction score) with navigated and conventional TKA at ve years follow up. (27) similar result reported by Rajkumar Selvanagayam et al by comparing functional outcome (knee society, WOMAC scale) at follow up of minimum 4 years, even though better accuracy was (18) associated with navigation-assisted system. Kim YH et al showed that no differences in components alignment, clinical function and components survival between the computer navigational TKR knees and conventional TKR knees.…”
Section: Discussionsupporting
confidence: 83%
“…While Harvie et al reported no difference in functional outcome (Knee society, SF 36, WOMAC scale and patient satisfaction score) with navigated and conventional TKA at ve years follow up. (27) similar result reported by Rajkumar Selvanagayam et al by comparing functional outcome (knee society, WOMAC scale) at follow up of minimum 4 years, even though better accuracy was (18) associated with navigation-assisted system. Kim YH et al showed that no differences in components alignment, clinical function and components survival between the computer navigational TKR knees and conventional TKR knees.…”
Section: Discussionsupporting
confidence: 83%
“…Twenty‐one of the included studies compared clinical outcomes between CAS‐ and CON‐TKA 8,31–40,42–51 . Most of these studies reported no significant differences in all clinical outcome measures, including KSS knee and function scores, WOMAC scores, HSS scores, and ROM, regardless of the follow‐up time 8,31,32,34,36,37,39,43–47,49–51 . However, the results of six studies suggested that CAS‐TKA could improve post‐operative clinical outcomes 33,35,38,40,42,48 .…”
Section: Resultsmentioning
confidence: 99%
“…As a passive system, CAS shows the position of surgical tools and the prosthesis within a patient's fixed reference system, enabling the surgeon to navigate through virtual pictures on a screen while handling these components 4 . Several comparative studies have demonstrated that CAS can provide better precision in bone cutting, mechanical alignment restoration and prosthesis positioning in TKA when compared with conventional instrumentation 5–11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the growing demand for technical accuracy and precision, computerassisted system (CAS) has rapidly developed and been well applied. A number of comparative research has demonstrated that CAS was able to minimize cases of outliers in MA and component position in comparison with conventional instrumentations [7][8][9]. Nevertheless, utilizing CAS would take longer surgery time and is related to higher cost [4].…”
Section: Introductionmentioning
confidence: 99%